Detection of ATM germline variants by the p53 mitotic centrosomal localization test in BRCA1/2-negative patients with early-onset breast cancer. Issue 1 (December 2016) - Prodosmo, Andrea; Buffone, Amelia; Mattioni, Manlio; Barnabei, Agnese; Persichetti, Agnese; De Leo, Aurora; Appetecchia, Marialuisa; Nicolussi, Arianna; Coppa, Anna; Sciacchitano, Salvatore; Giordano, Carolina; Pinnarò, Paola; et al.
Abstract Background VariantATM heterozygotes have an increased risk of developing cancer, cardiovascular diseases, and diabetes. Costs and time of sequencing andATM variant complexity make large-scale, general population screenings not cost-effective yet. Recently, we developed a straightforward, rapid, and inexpensive test based on p53 mitotic centrosomal localization (p53-MCL) in peripheral blood mononuclear cells (PBMCs) that diagnoses mutantATM zygosity and recognizes tumor-associatedATM polymorphisms. Methods Fresh PBMCs from 496 cancer patients were analyzed by p53-MCL: 90 cases with familialBRCA1/2- positive and -negative breast and/or ovarian cancer, 337 with sporadic cancers (ovarian, lung, colon, and post-menopausal breast cancers), and 69 with breast/thyroid cancer. Variants were confirmed byATM sequencing. Results A total of seven individuals with ATM variants were identified, 5/65 (7.7 %) in breast cancer cases of familial breast and/or ovarian cancer and 2/69 (2.9 %) in breast/thyroid cancer. No variantATM carriers were found among the other cancer cases. Excluding a single case in which bothBRCA1 andATM were mutated, no p53-MCL alterations were observed inBRCA1/2 -positive cases. Conclusions These data validate p53-MCL as reliable and specific test for germlineATM variants, confirmATM as breast cancer susceptibility gene, and highlight a possible association with breast/thyroid cancers.